Pengelolaan Wakaf Tunai dalam Pemberdayaan UMKM di Lingkungan Pondok Pesantren - Ulin Nisa; Betty Eliya Rokhmah (Penerbit Goodwood, 2022)
Purpose: The purpose of this study is to describe how the management of cash waqf in empowering small and medium enterprises in the Islamic boarding school environment. Productive waqf is one of the schemes for allocating funds from the people to be developed to be more productive. From these funds, it is hoped that the benefits will be able to generate a sustainable surplus. Waqf donations in the form of money or commonly called cash waqf can be a start so that managed waqf funds become a source of enduring funds for financing the needs of the people (productive waqf). Research Methodology: This study uses a qualitative method. Sources of data used are primary data in the form of managers and customers, while secondary data comes from documents, books, pictures and books. Data collection techniques using interview techniques, observation, and documentation. Data analysis in this study used the Miles and Huberman model. Result: The results showed that BWM Al-Mansur offers 1 program, namely a loan using a qardh contract with a margin of 3% every year. After the customer has done the financing, the customer will get business assistance which is carried out once a week. In financing, BWM is jointly and severally responsible for the members until there is an increase in business, this shows that cash waqf is enough to help empower MSMEs. Limitation: This research is limited to the management and empowerment of MSMEs and has not seen how the influence of cash waqf on a macro basis. Contribution: The results of this study are expected to provide an overview of cash waqf on the empowerment of MSMEs and can take policies related to cash waqf.